2003
DOI: 10.1542/peds.111.4.777
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Analyses of Mortality in Trisomy 13 and Trisomy 18

Abstract: Although survival is greatly affected by trisomy 13 and trisomy 18, 5% to 10% of people with these conditions survive beyond the first year of life. These population-based data are useful to clinicians who care for patients with these trisomies or counsel families with infants or fetuses who have a diagnosis of trisomy 13 or 18.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

43
384
11
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(445 citation statements)
references
References 41 publications
43
384
11
7
Order By: Relevance
“…In a population-based study by Embleton et al [1996], the major causes of death were cited as apnea and withdrawal of treatment. Another populationbased study by Rasmussen et al [2003] showed that the presence of a congenital heart defect did not seem to affect survival. A support group-based study by Baty et al [1994] showed the major cause of death as cardiopulmonary arrest.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a population-based study by Embleton et al [1996], the major causes of death were cited as apnea and withdrawal of treatment. Another populationbased study by Rasmussen et al [2003] showed that the presence of a congenital heart defect did not seem to affect survival. A support group-based study by Baty et al [1994] showed the major cause of death as cardiopulmonary arrest.…”
Section: Discussionmentioning
confidence: 97%
“…Patients with trisomy 18 have prenatal-onset severe growth retardation, characteristic craniofacial features, various visceral and skeletal malformations, and significant psychomotor mental retardation [Carey, 2001]. Several populationbased studies showed a remarkably reduced lifespan, with survival rates at age 1 year from 0 to 10% and with median survival time from 3 to 14.5 days [Carter et al, 1985;Young et al, 1986;Goldstein and Nielsen, 1988;Root and Carey, 1994;Embleton et al, 1996;Naguib et al, 1999;Nembhard et al, 2001;Brewer et al, 2002;Rasmussen et al, 2003]. The major causes of death were reported to be apnea and withdrawal of treatment [Embleton et al, 1996], and the presence of a congenital heart defect did not seem be associated with early death [Embleton et al, 1996;Rasmussen et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…(Although ultimately fatal, some reports estimate that 5 to 25% of infants with trisomy 18 survive the first year. 5,6,28 ) Specifically, several families felt that terminology was fatalistic to encourage them to choose an induced abortion rather than to continue the pregnancy, a theme echoed in a similar study of families receiving a prenatal diagnosis of holoprosencephaly. 16 The possibility of any life, however brief, was important to many of the families in our study.…”
Section: Discussionmentioning
confidence: 99%
“…5 Recent studies document that 50% of liveborn infants with trisomy 18 survive beyond the first week of life, 1 with 5 to 10% surviving beyond the first year. 3,6 Recent studies show that maternal serum and ultrasound screening procedures can detect over 80% of pregnancies affected with trisomy 18. 4 Prenatal ultrasound is widely perceived by expectant families to be a social event and a pleasant opportunity to see and meet their baby.…”
Section: Introductionmentioning
confidence: 99%
“…Withholding or withdrawal of intensive treatment (cesarean, resuscitation, respiratory support, and surgery) has been recommended because of the short life span (median survival time: 10-15 days; survival at age 1 year 5-10% [Rasmussen et al, 2003]) and profound mental retardation by many in the medical literatures [Bos et al, 1992;Paris et al, 1992]. Some authors indicated that management should be individualized and intensive treatment could be considered, placing significant weight on parental decision making in the context of the "best interests of the child" [Carey, 2005;Jones, 2006].…”
mentioning
confidence: 99%